Predicting maximal oxygen uptake from a 3-minute progressive knee-ups and step test - Yu-Chun Chung (PeerJ, 2021)
Background Cardiorespiratory fitness assessment is crucial for diagnosing health risks and assessing interventions. Direct measurement of maximum oxygen uptake (V̇O2 max) yields more objective and accurate results, but it is practical only in a laboratory setting. We therefore investigated whether a 3-min progressive knee-up and step (3MPKS) test can be used to estimate peak oxygen uptake in these settings. Method The data of 166 healthy adult participants were analyzed. We conducted a V̇O2 max test and a subsequent 3MPKS exercise test, in a balanced order, a week later. In a multivariate regression model, sex; age; relative V̇O2 max; body mass index (BMI); body fat percentage (BF); resting heart rate (HR0); and heart rates at the beginning as well as at the first, second, third, and fourth minutes (denoted by HR0, HR1, HR2, HR3, and HR4, respectively) during a step test were used as predictors. Moreover, R2 and standard error of estimate (SEE) were used to evaluate the accuracy of various body composition models in predicting V̇O2max. Results The predicted and actual V̇O2 max values were significantly correlated (BF% model: R2 = 0.624, SEE = 4.982; BMI model: R2 = 0.567, SEE = 5.153). The BF% model yielded more accurate predictions, and the model predictors were sex, age, BF%, HR0, ΔHR3−HR0, and ΔHR3−HR4. Conclusion In our study, involving Taiwanese adults, we constructed and verified a model to predict V̇O2 max, which indicates cardiorespiratory fitness. This model had the predictors sex, age, body composition, and heart rate changes during a step test. Our 3MPKS test has the potential to be widely used in epidemiological research to measure V̇O2 max and other health-related parameters.